Welfare Indicators for Aquaculture Research: Toolboxes for Five Farmed European Fish Species - Chris Noble; Wout Abbink; René Alvestad; László Ardó; Marie‐Laure Bégout; Nina Bloecher; Erik Burgerhout; Josep Calduch‐Giner; Mauro Chivite‐Alcalde; Petr Císař; Evan Durland; Åsa M. Espmark; et al. (Reviews in Aquaculture, 2026)
Refining approaches to measuring, monitoring and appraising animal welfare in aquaculture research is key to (i) protecting and optimizing it, (ii) documenting the severity of how and when it deviates, and (iii) ensuring good scientific quality, reliable results and reproducibility, amongst other factors. However, different fish species and life stages can have varying welfare needs and assessing their welfare can be challenging. An array of welfare indicators (WIs) can be utilized when documenting fish welfare, and there is currently little consensus on which WIs are most applicable to the key fish species used in European aquaculture research. The aim of this review is to propose updated, fit for purpose and comprehensive WI toolboxes for aquaculture research involving Atlantic salmon ( Salmo salar ), rainbow trout ( Oncorhynchus mykiss ), European seabass ( Dicentrarchus labrax ), gilthead seabream ( Sparus aurata ), and the common carp ( Cyprinus carpio ). Where possible, these toolboxes will also include life‐stage considerations. It also provides information on utilizing WIs in deciding humane end‐points as well as information on how to sample different types of indicators. The review closes with information on how digitalization can affect the collection, collation and analysis of WI data in aquaculture research, including both practical and theoretical considerations. The toolboxes incorporate a range of WIs that go beyond those required for legally safeguarding fish welfare in both laboratory and operational experimental facilities in the current European 2010/63/EU Directive on the protection of animals used for scientific purposes and its amendment, the Commission Delegated Directive (EU) 2024/1262.

Protected area coverage of vulnerable regions to conserve functional diversity of birds - Carlos Martínez‐Núñez; Ricardo Martínez‐Prentice; Vicente García‐Navas (Conservation Biology, 2023)
Global‐change drivers are increasing the rates of species extinction worldwide, posing a serious threat to ecosystem functioning. Preserving the functional diversity of species is currently a priority to mitigate abrupt biodiversity loss in the coming decades. Therefore, understanding what factors better predict functional diversity loss in bird assemblages at a global scale and how existing protected areas cover the most vulnerable regions is of key importance for conservation. We examined the environmental factors associated with the risk of functional diversity loss under 3 scenarios of bird species extinction based on species distribution range size, generation length, and International Union for the Conservation of Nature conservation status. Then, we identified regions that deserve special conservation focus. We also assessed how efficiently extant terrestrial protected areas preserve particularly vulnerable bird assemblages based on predicted scenarios of extinction risk. The vulnerability of bird functional diversity increased as net primary productivity, land‐use diversity, mean annual temperature, and elevation decreased. Low values for these environmental factors were associated with a higher risk of functional diversity loss worldwide through two mechanisms: one independent of species richness that affects assemblages with low levels of niche packing and high functional dissimilarity among species, and the other that affects assemblages with low species richness and high rates of extinction. Existing protected areas ineffectively safeguarded regions with a high risk of losing functional diversity in the next decades. The global predictors and the underlying mechanisms of functional vulnerability in bird assemblages we identified can inform strategies aimed at preserving bird‐driven ecological functions worldwide.

Enzymatic Hydrolysis of Pacific White Shrimp Residue ( Litopenaeus vannamei ) with Ultrasound Aid - José Stênio Aragão Rebouças Júnior; Vilásia Guimarães Martins; Carlos Prentice-Hernández; José Maria Monsserrat; Marcelo Borges Tesser; Juliana Machado Latorres (Journal of Aquatic Food Product Technology, 2022)

Effect of In Vitro Gastrointestinal Digestion on the Bioactive Properties of Mullet ( Mugil liza ) Peptides - Camila da Costa de Quadros; Juliana Machado Latorres; Mariano Michelon; Myriam de las Mercedes Salas-Mellado; Carlos Prentice (Journal of Aquatic Food Product Technology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Bioactivity of the Protein Hydrolysates Obtained from the Most Abundant Crustacean Bycatch - Tavani R. Camargo; Paulo Mantoan; Patrícia Ramos; José M. Monserrat; Carlos Prentice; Célio C. Fernandes; Willian F. Zambuzzi; Wagner C. Valenti (Marine Biotechnology, 2021)

Optimization of a low-cost fertilizer-based medium for large-scale cultivation of the coastal diatom Conticribra weissflogii using response surface methodology and its effects on biomass composition - Cynthia Couto; Carlos Prentice Hernández; Rui Carlos M. Alves Sobrinho; Carlos Rafael Borges Mendes; Fabio Roselet; Paulo Cesar Abreu (Journal of Applied Phycology, 2021)

Zootechnical performance, biochemical response, and chromaticity in Pacific white shrimp (Litopenaeus vannamei) (Boone, 1931) after the inclusion of lyophilized açaí (Euterpe oleracea) in the diet - Shadai M. Silva; Patricia B. Ramos; Juan R. Buitrago; Thamyres V. N. da Silva; Cleber S. Simião; Grecica M. Colombo; Marcos Schmitz; Marcelo B. Tesser; Carlos Prentice; Wilson Wasielesky; José M. Monserrat (Aquaculture International, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Functional Properties of White Shrimp ( Litopenaeus vannamei ) By-Products Protein Recovered by Isoelectric Solubilization/Precipitation - Adriana De Souza Abreu; Michele Moraes De Souza; Meritaine Da Rocha; Wilson Francisco Wasielesky; Carlos Prentice (Journal of Aquatic Food Product Technology, 2019)

Evaluation of the Antioxidant and Antimicrobial Activity of Protein Hydrolysates and Peptide Fractions Derived from Colossoma macropomum and Their Effect on Ground Beef Lipid Oxidation - Camila Da Costa De Quadros; Karina Oliveira Lima; Caio Hendrix Luz Bueno; Fabíola Helena dos Santos Fogaça; Meritaine Da Rocha; Carlos Prentice (Journal of Aquatic Food Product Technology, 2019)

Anti-Inflammatory, Antioxidant, and Antimicrobial Effects of Underutilized Fish Protein Hydrolysate - Meritaine Da Rocha; Ailén Alemán; Gyselle Chrystina Baccan; M. Elvira López-Caballero; Carmen Gómez-Guillén; Pilar Montero; Carlos Prentice (Journal of Aquatic Food Product Technology, 2018)

Peptides from Fish By-product Protein Hydrolysates and Its Functional Properties: an Overview - Juan Zamora-Sillero; Adem Gharsallaoui; Carlos Prentice (Marine Biotechnology, 2018)

Effect of Organic Acids on Physical-Mechanical and Antifungicidal Properties of Anchovy Protein Films - Meritaine da Rocha; Luciana Prietto; Michele Moraes de Souza; Eliana Badiale Furlong; Carlos Prentice (Journal of Aquatic Food Product Technology, 2018)

Evaluation of the Antioxidant Activity In Vitro and in Hippocampal HT-22 Cells System of Protein Hydrolysates of Common Carp ( Cyprinus carpio ) By-Product - Juan Zamora-Sillero; Patrícia Ramos; José María Monserrat; Carlos Prentice (Journal of Aquatic Food Product Technology, 2018)

Physicochemical, Microbiological, and Sensory Properties of Pâté Elaborated from Whitemouth Croaker ( Micropogonias furnieri ) Muscle - Marcy Heli Paiva Rodrigues; Camila da Costa De Quadros; Paola Lopes Cavalheiro; Michele Moraes De Souza; Carlos Prentice (Journal of Aquatic Food Product Technology, 2017)

Do soil and climate properties drive biogeography of the Australian proteaceae? - Emily Prentice; Nunzio Knerr; Alexander N. Schmidt-Lebuhn; Carlos E. González-Orozco; Elisabeth N. Bui; Shawn Laffan; Joseph T. Miller (Plant and Soil, 2017)

Physicochemical and Functional Properties of Protein Recovered from Fish Waste - Irene Rodrigues Freitas; William Renzo Cortez-Vega; Carlos Prentice (Journal of Aquatic Food Product Technology, 2016)

Effects of Protein Concentration, Plasticiser, and pH on the Properties of Protein Films from Whitemouth Croaker ( Micropogonias furnieri ) Residues - Shanise Lisie Mello El Halal; Elessandra da Rosa Zavareze; Annie Campello Telles; Ricardo Marques e Silva; Márcia de Mello Luvielmo; Carlos Prentice (Journal of Aquatic Food Product Technology, 2016)

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

Comparing and evaluating process‐based ecosystem model predictions of carbon and water fluxes in major European forest biomes - Pablo Morales; Martin T. Sykes; I. Colin Prentice; Pete Smith; Benjamin Smith; Harald Bugmann; Bärbel Zierl; Pierre Friedlingstein; Nicolas Viovy; Santi Sabaté; Anabel Sánchez; Eduard Pla; et al. (Global Change Biology, 2005)
Process‐based models can be classified into: (a) terrestrial biogeochemical models (TBMs), which simulate fluxes of carbon, water and nitrogen coupled within terrestrial ecosystems, and (b) dynamic global vegetation models (DGVMs), which further couple these processes interactively with changes in slow ecosystem processes depending on resource competition, establishment, growth and mortality of different vegetation types. In this study, four models – RHESSys, GOTILWA+, LPJ‐GUESS and ORCHIDEE – representing both modelling approaches were compared and evaluated against benchmarks provided by eddy‐covariance measurements of carbon and water fluxes at 15 forest sites within the EUROFLUX project. Overall, model‐measurement agreement varied greatly among sites. Both modelling approaches have somewhat different strengths, but there was no model among those tested that universally performed well on the two variables evaluated. Small biases and errors suggest that ORCHIDEE and GOTILWA+ performed better in simulating carbon fluxes while LPJ‐GUESS and RHESSys did a better job in simulating water fluxes. In general, the models can be considered as useful tools for studies of climate change impacts on carbon and water cycling in forests. However, the various sources of variation among models simulations and between models simulations and observed data described in this study place some constraints on the results and to some extent reduce their reliability. For example, at most sites in the Mediterranean region all models generally performed poorly most likely because of problems in the representation of water stress effects on both carbon uptake by photosynthesis and carbon release by heterotrophic respiration ( R h ). The use of flux data as a means of assessing key processes in models of this type is an important approach to improving model performance. Our results show that the models have value but that further model development is necessary with regard to the representation of the some of the key ecosystem processes.